Taxing corporate income - Alan J. Auerbach; Michael P. Devereux; Helen Simpson (Center for Economic Studies and ifo Institute (CESifo), 2007)
Following Meade (1978), we reconsider issues in the design of taxes on corporate income. We outline developments in economies and in economic thought over the last thirty years, and investigate how these developments should affect the design of taxes on corporate income. We consider a number of tax systems which have been proposed, distinguishing them in two main dimensions: the definition of what is to be taxed, and where it is to be taxed. We propose that a tax levied on economic rent accruing in the corporate sector, and on a destination basis, merits serious consideration. We discuss alternative approaches, including both R-based and R+F-based flow-of-funds taxes and an ACE allowance. It is the destination basis - with border adjustments for exports and imports - which primarily distinguishes our proposals from those of Meade (1978).
Keywords: H2; H3; 330; Unternehmensbesteuerung; Steuersystem; Großbritannien; Vergleich; Welt